Memória coletiva e as tradições sagradas: relatos de homens e mulheres na aldeia Munduruku de Juara/MT - Freytag, Rosane Salete (2014)
In front of the changes processed within the Brazilian indigenous villages occurred by the new model of social, economic and technological relations process, Juaras's indigenous village Munduruku/MT, live a new moment, a fusion between the culture of Indian man and not indian. This work is named as a change occurred by 'acculturation interaction' constituted by the contact with non-Indian society. This is a time of adjustment and questioning of the Amerindian people, because there are strong indications of a possible cultural bottleneck of the knowledge inherited from the ancient ethnicity, which could transform the villagers's life. Meanwhile, the survey sought the method of oral history, with applications of interviews with the village's residents. Through them, we tried to visualize the participation of men and women in Amerindian universe. The found differed itself from the original proposed project, because the Munduruku's gender relation is very close to the non - Indian man model. For this reason, the search was adjusted to what was found at the village and what became evident, the work was done in three moments: at first, the return to the historical context of the indigenous population in Amazon and specifically in Mato Grosso state. At second, the characterization Munduruku comunity, subjects of the investigation and residents in the municipality of Juara / MT, is evidencing their culture, in a comparative study of the representation of faith, belief and ritual between the myth of Christian creation and Amerindian. At third, a pontual work about gender, highlighting the relationship between men and women, under the contribution of the sacred and the profane.